Total quality management and operational excellence text with cases - Oakland, John S. (Routledge, 2014)
Total Quality Management and Operational Excellence: Text with Cases (Fourth Edition) is supplemented for the first time with a suite of online teaching aids for busy tutors. This exciting update of a classic text is perfect for all students studying for professional qualifications in the management of quality, or those studying science, engineering or business and management who need to understand the part TQM may play in their subjects